Whodunit to Irene Adler? From “the Woman” to “the Dominatrix” – on the Transformation of the Heroine in the Adapting Process and Her Representation in the Sherlock Miniseries - Popłońska, Magdalena (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2014)
One of the peculiar characteristics of the Sherlock Holmes fandom is that it has always had a tendency to blow innuendos in Arthur Conan Doyle’s stories out of proportion. One might argue that such is the case of Irene Adler, the most recognisable female character from the Sherlock Holmes canon. Although we are not given much information on her in the original story and she hardly speaks in her own voice, for the community of readers she has become the most significant woman that Sherlock Holmes had ever encountered. Thus, the creators who adapted her for the screen also treated the heroine of “A Scandal in Bohemia” symbolically, allowing themselves to freely portray her presence in their versions of the story. For certain reasons, Irene Adler has been interpreted in pop-culture differently at various times: as the woman who beat Holmes with her wit, the detective’s romantic interest, his nemesis or a femme fatale figure. This tendency seems to be pushed to the extreme recently and the adaptations of the heroine in question gravitate towards a sexually confident, overtly self-aware, as well as dominant (both sexually and mentally) rival to Holmes. The idea behind this paper is to investigate the transformation of Irene Adler’s character from the originally debatably scandalous adventuress to her modern portrayal as a dominatrix in the BBC miniseries, Sherlock. Hence, I will concentrate on this most recent take on the woman in the episode “A Scandal in Belgravia,” attempting to analyse in what ways the creators of the show go back to the roots and succeed in capturing the essence of Irene Adler’s figure, and conversely – in what measure does this adaptation epitomize the changes done to the character over the years of reinterpreting and diverting from its literary counterpart.